ANALYTICAL MODEL FOR DETERMINING THE FRICTION FORCE AT THE CONTACT OF A METAL BODY WITH A COPPER CONTACT SURFACE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents the development of an analytical model for calculating the frictional force when a copper contact surface slides across a static metallic body. Available analytical tribological models and mathematical methods were used to create the model. This model can be used to obtain information about the barrel wear of an artillery gun.